Enantioselective Synthesis of Atropisomers by Oxidative Aromatization with Central-to-Axial Conversion of Chirality - Clément Lemaitre; Stefania Perulli; Ophélie Quinonero; Cyril Bressy; Jean Rodriguez; Thierry Constantieux; Olga García Mancheño; Xavier Bugaut (Molecules, 2023)
Atropisomers are fascinating objects of study by themselves for chemists but also find applications in various sub-fields of applied chemistry. Obtaining them in enantiopure form is far from being a solved challenge, and the past decades has seen a surge of methodological developments in that direction. Among these strategies, oxidative aromatization with central-to-axial conversion of chirality has gained increasing popularity. It consists of the oxidation of a cyclic non-aromatic precursors into the corresponding aromatic atropisomers. This review proposes a critical analysis of this research field by delineating it and discussing its historical background and its present state of the art to draw potential future development directions.